1981
DOI: 10.1063/1.442267
|View full text |Cite
|
Sign up to set email alerts
|

An ESR and ENDOR study of tunneling rotation of a hindered CH3 group in C2H5 radicals trapped in xenon matrices at 4.2 K: Environment effect on internal rotation

Abstract: Two kinds of ethyl radicals have been observed in Xe matrices depending upon the reactions of radical formation. The CH3 group in C2H5(I) formed from H abstraction by H atoms at temperatures below 50 K exhibits an ESR hyperfine pattern characteristic of tunneling rotation in a threefold hindering potential, whereas that in C2H5(II) formed from homolytic scission of the C–H bond exhibits a conventional spectrum typical of free or random hopping rotation with a small barrier. The g and hyperfine coupling tensors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…[33][34][35][36] On the basis of this model, EPR and ENDOR spectra of organic radicals containing methyl rotors have been extensively described. [37][38][39][40][41][42][43] Those studies used the hyperfine splittings and the thermal evolution of the magnetic resonance signals to characterize the shape and depth of the rotational well that causes the hindrance of the methyl motion.…”
Section: Analysis Of the Results: Methyl Rotation Modelmentioning
confidence: 99%
“…[33][34][35][36] On the basis of this model, EPR and ENDOR spectra of organic radicals containing methyl rotors have been extensively described. [37][38][39][40][41][42][43] Those studies used the hyperfine splittings and the thermal evolution of the magnetic resonance signals to characterize the shape and depth of the rotational well that causes the hindrance of the methyl motion.…”
Section: Analysis Of the Results: Methyl Rotation Modelmentioning
confidence: 99%
“…6 The μ þ is produced 100% spin polarized at a nuclear accelerator (TRIUMF in the present study) and this polarization can be effectively transfered to a free radical by Mu addition reactions, and then sensitively monitored by the μSR (muon spin relaxation or resonance) technique. [6][7][8][9][10][11][12][13][14] The most extensive studies of Hfcc in alkyl radicals to date has been for the ethyl radical and its isotopomers, both by EPR 1,5,12,15 and μSR 12,14 (see also citations in ref 11). Of relevance here are the torsional barriers to internal rotation.…”
Section: Introductionmentioning
confidence: 99%
“…The measured value of the isotropic hfi, 141, is about 60 MHz and provides the most direct way of determining spin densities in organic free radical^.^ McConnell's study of the anisotropic hfi in malonic acidlo demonstrated that the sign of a is negative.…”
Section: Introductionmentioning
confidence: 99%